A fast, sensitive and fluorescent LPMO activity assay - Ipsen, Johan Ø.; Johansen, Katja S.; Brander, Søren (Frontiers in Microbiology, 2023)
Lytic polysaccharide monooxygenases (LPMOs) are industrially relevant enzymes that utilize a copper co-factor and an oxygen species to break down recalcitrant polysaccharides. These enzymes are secreted by microorganisms and are used in lignocellulosic refineries. As such, they are interesting from both the ecological/biological and industrial perspectives. Here we describe the development of a new fluorescence-based kinetic LPMO activity assay. The assay is based on the enzymatic production of fluorescein from its reduced counterpart. The sensitivity of the assay is in the range of 1 nM LPMO with optimized assay conditions. Furthermore, the reduced fluorescein substrate can also be used to identify peroxidase activity as seen by the formation of fluorescein by horseradish peroxidase. The assay was shown to work well at relatively low H2O2 and dehydroascorbate concentrations. The applicability of the assay was demonstrated.